2022
DOI: 10.3390/ijms23179956
|View full text |Cite
|
Sign up to set email alerts
|

SP and KLF Transcription Factors in Cancer Metabolism

Abstract: Tumor development and progression depend on reprogramming of signaling pathways that regulate cell metabolism. Alterations to various metabolic pathways such as glycolysis, oxidative phosphorylation, lipid metabolism, and hexosamine biosynthesis pathway are crucial to sustain increased redox, bioenergetic, and biosynthesis demands of a tumor cell. Transcription factors (oncogenes and tumor suppressors) play crucial roles in modulating these alterations, and their functions are tethered to major metabolic pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 127 publications
(153 reference statements)
1
13
0
Order By: Relevance
“…They found that in breast cancer, KLF4 could upregulate the expression of PFKP by directly binding to the PFKP promoter. More interestingly, research has shown that SP and KLF are involved in cancer metabolism, cell proliferation, apoptosis, inflammation, and tumorigenesis 85 , 86 . These data suggested that the transcription factors SP and KLF may be involved in the occurrence and development of cancer by PFKP, but more data are needed to support this hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…They found that in breast cancer, KLF4 could upregulate the expression of PFKP by directly binding to the PFKP promoter. More interestingly, research has shown that SP and KLF are involved in cancer metabolism, cell proliferation, apoptosis, inflammation, and tumorigenesis 85 , 86 . These data suggested that the transcription factors SP and KLF may be involved in the occurrence and development of cancer by PFKP, but more data are needed to support this hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…KLFs is a class of transcription factors, which plays an important role in the regulation of cell proliferation, differentiation and embryonic development [19]. Currently, some studies have proved that KLF7 is highly correlated with the occurrence and development of tumor cells [20], and it can be used as a molecular marker for some cancers with adverse effects after rain.…”
Section: Discussionmentioning
confidence: 99%
“…SP/KLF proteins are members of a transcription factor family that is characterized by three highly conserved zinc fingers that interact with DNA. Investigators have demonstrated the presence of SP/KLF transcription factors in many tissues and that they regulate cellular proliferation, differentiation, apoptosis, and tumorigenesis ( 32 ). As a member of this family, KLF14 occupies unique positions in signaling pathways, proliferation, and cellular differentiation.…”
Section: Discussionmentioning
confidence: 99%